Radiotherapy in pediatric pilocytic astrocytomas: A subgroup analysis within the prospective multicenter study HIT-LGG 1996 by the German Society of Pediatric Oncology and Hematology (GPOH) - Mueller, K.; Gnekow, A.; Falkenstein, F.; Scheiderbauer, J.; Zwiener, I.; Pietsch, T.; Warmuth-Metz, M.; Voges, J.; Nikkhah, G.; Flentje, M.; Combs, S. E.; Vordermark, D.; et al. (Strahlentherapie und Onkologie, 2013)
Purpose: We evaluated clinical outcomes in the subset of patients who underwent radiotherapy (RT) due to progressive pilocytic astrocytoma within the Multicenter Treatment Study for Children and Adolescents with a Low Grade Glioma HIT-LGG 1996. Patients and methods: Eligibility criteria were fulfilled by 117 patients. Most tumors (65 %) were located in the supratentorial midline, followed by the posterior fossa (26.5 %) and the cerebral hemispheres (8.5 %). Median age at the start of RT was 9.2 years (range 0.7-17.4 years). In 75 cases, external fractionated radiotherapy (EFRT) was administered either as first-line nonsurgical treatment (n = 58) or after progression following primary chemotherapy (n = 17). The median normalized total dose was 54 Gy. Stereotactic brachytherapy (SBT) was used in 42 selected cases. Results: During a median follow-up period of 8.4 years, 4 patients (3.4 %) died and 33 (27.4 %) experienced disease progression. The 10-year overall (OS) and progression-free survival (PFS) rates were 97 and 70 %, respectively. No impact of the RT technique applied (EFRT versus SBT) on progression was observed. The 5-year PFS was 76 ± 5 % after EFRT and 65 ± 8 % after SBT. Disease progression after EFRT was not influenced by gender, neurofibromatosis type 1 (NF1) status, tumor location (hemispheres versus supratentorial midline versus posterior fossa), age or prior chemotherapy. Normalized total EFRT doses of more than 50.4 Gy did not improve PFS rates. Conclusion: EFRT plays an integral role in the treatment of pediatric pilocytic astrocytoma and is characterized by excellent tumor control. A reduction of the normalized total dose from 54 to 50.4 Gy appears to be feasible without jeopardizing tumor control. SBT is an effective treatment alternative. © 2013 Springer Heidelberg Berlin.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Brachytherapy; Dose-response relationship; Glioma; Pediatric; Progression-free survival